Drug Reaction with Eosinophilia and Systemic Symptoms Syndrome following Dalbavancin and Oritavancin Administration in a Patient with Osteomyelitis - Bai, Jina; Preciado, Emily Frech; Harlow, Mary Baxter; Blank, Nina (Case reports in dermatology, 2025)
Introduction: Dalbavancin and oritavancin are newer long-acting antibiotics with potent activity against gram-positive organisms, including methicillin-resistant Staphylococcus aureus (MRSA). To our knowledge, there have been no reported cases of drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome in a patient treated with dalbavancin and oritavancin. Patient Presentation: A woman in her 20s presented with a right thumb abscess and cellulitis that failed to respond to several courses of oral antibiotics, resulting in recurrent emergency room visits over 3 weeks. Approximately 1 month after the initial skin infection, magnetic resonance imaging revealed osteomyelitis of the right thumb. She was treated with a single dose of oritavancin followed by two weekly doses of dalbavancin, which successfully resolved the infection. However, she subsequently developed fever and a rash consistent with DRESS syndrome, likely triggered by oritavancin or dalbavancin. Given the prolonged half-life of these medications, she required treatment with high-dose steroids for an extended duration. Conclusion: Dalbavancin and oritavancin are second-generation lipoglycopeptide antibiotics that provide coverage for gram-positive organisms, including MRSA. They are approved for the treatment of acute bacterial skin and skin structure infections and are used off-label for bacteremia, endocarditis, and osteomyelitis. Their prolonged half-lives – 257 h for dalbavancin and 195 h for oritavancin – allow for less frequent dosing. However, a long half-life also leads to prolonged drug exposure in the event of adverse effects. Here, we report the first case of DRESS syndrome in a patient treated with dalbavancin and oritavancin.